STUNTING PREVENTION THROUGH A COMBINATION OF NUTRITION EDUCATION AND SIMULATION GAMES - Putri Widita Muharyani; Nurna Ningsih; Karolin Adhisty; Herliawati Herliawati; Gaviota Khalish; Yodias Gloria Kusuma Putri (LPPM Universitas Flores, 2026)
Stunting is a chronic malnutrition problem caused by a long-term lack of nutritional intake due to food not meeting children's nutritional needs. It is important for the community, especially mothers of infants and toddlers, to have the knowledge and skills to meet children's nutritional needs to prevent stunting. The purpose of this community service activity is to empower the community to implement stunting prevention measures. The target of the activity is mothers with infants and toddlers in the Sako Community Health Centre working area. The method of implementation of the activity is community empowerment through educational activities using the SiDu Card simulation games. The results obtained before the community service activity were only 11 mothers (36.7%) who had good knowledge regarding stunting and fulfilling nutrition for children. After the education and simulation games, more than half of the mothers had good knowledge (76.7%). This community service activity was able to increase community knowledge regarding stunting and fulfilling nutritional needs for children. The necessary follow-up plan is regular monitoring and evaluation of the implementation of education carried out by the community health centre and cadres using the SiDu Card as one of the educational media related to fulfilling nutritional needs to prevent stunting in children.